2013
DOI: 10.1007/s12013-013-9706-5
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous Humor Rheology After Nd:YAG Laser Photo Disruption

Abstract: This work aimed to consider the hazardous side effect of eye floaters treatment with Q-switched Nd:YAG laser on the protein and viscoelastic properties of the vitreous humor, and evaluate the protective role of vitamin C against laser photo disruption. Five groups of New Zealand rabbits were divided as follows: control group for (n = 3) without any treatment, the second group (n = 9) treated with Q-switched Nd:YAG laser energy of 5 mJ × 100 pulse delivered to the anterior, middle, and posterior vitreous, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…While the composition and nature of vitreous humor has been the subject of considerable investigation,13,3740 there is no consensus on whether or how these factors influence drug distribution, nor are there robust data on interspecies differences in many aspects of vitreous composition. Indeed, while rabbit vitreous frequently is stated to be “more viscous” than that of other species (human, monkey), a conclusion that gross physical appearances of dissected vitreous supports, there is considerable debate in the field regarding how to most appropriately characterize the rheologic and mechanical properties of the vitreous 13,37,38,41,42. In existing ocular models, vitreous humor has been described alternately as a porous medium (e.g., Missel14), or a homogeneous viscous fluid (e.g., Schmitt19).…”
Section: Discussionmentioning
confidence: 99%
“…While the composition and nature of vitreous humor has been the subject of considerable investigation,13,3740 there is no consensus on whether or how these factors influence drug distribution, nor are there robust data on interspecies differences in many aspects of vitreous composition. Indeed, while rabbit vitreous frequently is stated to be “more viscous” than that of other species (human, monkey), a conclusion that gross physical appearances of dissected vitreous supports, there is considerable debate in the field regarding how to most appropriately characterize the rheologic and mechanical properties of the vitreous 13,37,38,41,42. In existing ocular models, vitreous humor has been described alternately as a porous medium (e.g., Missel14), or a homogeneous viscous fluid (e.g., Schmitt19).…”
Section: Discussionmentioning
confidence: 99%
“…Only by using pulse durations in the nanosecond-range and focusing the radiation, these laser systems can generate optical breakdowns, accompanied by generating cavitation bubbles. Contradictory statements have been made about the rheology of corpus vitreum in the literature: Whereas Krauss et al found no essential changes of the vitreous body 23 after Q-switch Nd:YAG laser irradiation, Abdelkawi et al could determine clear effects on vitreous body rheology (e.g., a change in protein content, refractive index, viscosity and consistency) 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the vitreous body exhibits rheological properties like a non-Newtonian fluid 23 25 , values of the viscosity are not clearly defined in the literature. Some data are given as dynamic viscosity adopted to Newton’s law as a Newtonian fluid, given in Eq.…”
Section: Discussionmentioning
confidence: 99%
“…50 Floaters are reported to have various compositions and sizes. 51 It is possible that part of the hyaloid vessel that breaks down at birth results in fragments that are also part of the floaters. 52 In adults, floaters are most likely caused by PVD but in adolescence, floaters most likely result from myopic vitreopathy.…”
Section: Diseases Associated With Liquefactionmentioning
confidence: 99%
“…A proposed treatment for floaters is focusing a laser onto the floater to disrupt the collagen strands of floaters. 51 A treatment proven effective is performing a vitrectomy. 50 Macular hole formation results from the VH pulling away from the retina and causing the macula to tear.…”
Section: Diseases Associated With Liquefactionmentioning
confidence: 99%